Meningkatkan Kemampuan Berbicara Melalui Media Gambar Pada Anak Taman Kanak-Kanak (TK) Tunas Palma Kerumutan - Vera Sriwahyuningsih; Mufadhal Barseli; Desi Afrianti (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
This Community Service (PKM) is carried out as a socialization and education activity for Tunas Palma Kerumutan Kindergarten (TK) children. This Community Service Activity (PKM) was carried out with the aim of describing how to improve children's speaking skills through the media of images. Based on the child's development, there are still many problems faced by kindergarten children such as difficulty speaking, connecting vocabulary for conversations in good and correct language in learning activities. Another goal of this activity is to facilitate optimal growth and development of children so that children prefer to play and socialize with their peers. This research was conducted using the literature review method and observed changes from before being given training to after being given training. Based on the results of the activities carried out by the UPI YPTK Padang PKM Team for Tunas Palma Kerumutan Kindergarten students, it can be concluded that media images have an influence on children's speaking abilities in Kindergarten (TK).